Clinical versus ultrasonographic fetal weight estimation and its correlation with actual birth weight - Ingale, Ashwini; Khade, Shweta Avinash; Shirodkar, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This is a prospective study was conducted at Obstetrics and Gynecology department, tertiary care Hospital, to compare the accuracy of clinical and ultrasonographic estimation of fetal weight at term with actual birth weight. Methods: The present study is a prospective comparative study of fetal weight estimation in Antenatal women with term gestation (37week to 42week of gestation) singleton pregnancy with vertex presentation, who had gestational age confirmed by dates and ultrasound scanning of< 22weeks admitted in tertiary care center from March 2016 to November 2016. Patients with Polyhydramnios, oligohydramnios, Antepartum hemorrhage, Congenital anomalies of fetus, Obese (Body mass index >30 kilogram/meter2) are excluded from the study. Estimation of fetal weight is done by clinical method and ultrasonography. Birth weight after delivery was recorded in grams by electronic weighing machine and tabulated. Results: Clinical as well as ultrasonography estimates observed to be strongly correlate with actual birth weight. Both the methods had more sensitivity in birth weight range 2500-4000gm than <2500g and >4000g. The overall mean absolute percentage error of the clinical method (7.2±7.7) was smaller than that of the sonographic method (16.2±11.1). In low birth-weight (<2,500g) group, mean absolute percentage error was 9.0±11.3 with USG and same with clinical was 11.7±9.0. No statistically significant difference was observed. Conclusions: The present study concludes that clinical estimation of birth-weight is as accurate as routine ultrasonographic estimation.Clinical palpation should be considered as diagnostic tool for FWE and is equally reliable even when done by trained medical person. It is cheap and easy to teach. The need is to practically apply this method in obstetrics and guide the management decisions.